Avoiding Cheap Grace: Luther and the Need for Moral Despair - Rehwaldt-Alexander, Jeremy (Dialog, 2006)
This article addresses two problems in the development of an adequate Lutheran ethics in our time: moral quietism in the public square and an overly narrow and individualistic moral vision. I argue that the construction of grace as “freedom” tends toward “cheap grace” and that grace needs, then, to be thought of as a compelling of moral striving. Second, I argue that our sense of moral despair today should be broadened to focus on our participation in social structures that damage humans and the nonhuman world as much as on our personal and individual failings.